Role of EPAC in cAMP-Mediated Actions in Adrenocortical Cells - Lewis, Aurélia E.; Aesoy, Reidun; Bakke, Marit (Frontiers in Endocrinology, 2016)
Adrenocorticotropic hormone (ACTH) regulates adrenal steroidogenesis mainly via the intracellular signalling molecule cAMP. The effects of cAMP are principally relayed by activating protein kinase A (PKA) and the more recently discovered exchange proteins directly activated by cAMP 1 and 2 (EPAC1 and EPAC2). While the intracellular roles of PKA have been extensively studied in steroidogenic tissues, those of EPACs are only emerging. EPAC1 and EPAC2 are encoded by the genes RAPGEF3 and RAPGEF4, respectively. Whereas EPAC1 is ubiquitously expressed, the expression of EPAC2 is more restricted, and typically found in endocrine tissues. Alternative promoter usage of RAPGEF4 gives rise to three different isoforms of EPAC2 that vary in their N-termini (EPAC2A, EPAC2B and EPAC2C) and that exhibit distinct expression patterns. EPAC2A is expressed in the brain and pancreas, EPAC2B in steroidogenic cells of the adrenal gland and testis and, EPAC2C has until now only been found in the liver. In this review, we discuss current knowledge on EPAC expression and function with focus on the known roles of EPAC in adrenal gland physiology.